Mapping soil organic carbon stocks by combining NIR spectroscopy and stochastic vertical distribution models : a case study in the Mvoti River Catchment, KZN, South Africa - Wiese, Liesl (Stellenbosch : Stellenbosch University, 2019)
Thesis (PhDAgric)--Stellenbosch University, 2019.